KECERDASAN EMOSIONAL DAN TINGKAT KECEMASAN IBU: KEJADIAN STUNTING PADA BALITA DI KOTA KUPANG - Santa Luciana Diaz Vera da Costa; Jane Austen Peni; Astuti Nur; Asweros Umbu Zogara (Bajang Institute, 2024)
Stunting is a nutritional problem that adversely affects the quality of life of children in achieving optimal growth and development according to their genetic potential. An important period in child development is the toddler period, because during this time basic growth will affect the child's further development. A mother does not easily face the problem of stunting in her child, so good emotional intelligence is needed. Lack of adaptability in dealing with changes can cause psychosocial problems, one of which is anxiety. Mothers who are unable to adapt to changes in themselves who are married and have stunted toddlers can affect a mother's anxiety level. The purpose of the study was to determine the relationship between emotional intelligence and maternal anxiety to the incidence of stunting. The research method uses a cross sectional design. The sampling technique was accidental sampling, a total sample of 370 toddlers in Kupang City. Data analysis using chi-square test (p value <0.05). The results showed that there was a relationship between maternal anxiety and the incidence of stunting with a p value = 0.000 and there was no relationship between maternal emotional intelligence and the incidence of stunting with a p value = 0.787